Severe HELLP Syndrome Complicated by Multiorgan Impairment and DIC: The Role of Drain Placement: A Case Report - Bazoukis, Xenofontas; Khristianov, Alkistis Victoros; Pavlides, Giannis; Chasiotis, Athanasios; Kazakos, Ioannis (International Journal of Innovative Research in Medical Science, 2023)
Background: Disseminated intravascular coagulation (DIC) can present postpartumly in women with hemolysis, elevated liver enzymes, low platelets (HELLP) syndrome. This report highlights the importance of drain insertion following emergency cesarean section in anticipation of DIC. This would avoid the need of an open exploratory laparotomy procedure. Case: At 34 weeks of gestation, a P1G4 woman was diagnosed with severe pre-eclampsia and HELLP syndrome and her baby with intrauterine growth restriction (IUGR) and fetal distress. The woman received hydralazine, labetalol, methyl-dopa, magnesium sulphate and an emergency cesarean section was performed. A few hours later, the woman developed DIC. Red blood cells (RBC), fresh frozen plasma (FFP) and platelets (PLTs) were administered and an abdominal CT was performed, revealing intra-abdominal and anterior rectus sheath haematomas. An open exploratory laparotomy was performed to identify areas of bleeding and a drain was inserted to monitor the bleeding. The woman was closely monitored and regained haemodynamic stability. Conclusion: DIC is a common postpartum complication in women diagnosed with HELLP syndrome. Preemptive drain insertion following cesarean section in these women could avoid the need for additional revision surgery should DIC occur. Clear guidelines on the topic are lacking. Teaching Points: Postpartum surgical drain placement in women diagnosed with HELLP syndrome who later develop DIC could avoid the need of additional surgery. Precis Preemptively placing a surgical drain following cesarean section in patients with HELLP syndrome may avoid additional surgery in patients that go on to develop DIC.